The relationship between the Dang Van criterion and the traditional bulk fatigue criteria - Peridas, G; Korsunsky, A; Hills, D (Professional Engineering Publishing, 2003)
A formal relationship is established between the traditional bulk fatigue criteria such as the Goodman rule and the Sines criterion, and the recent crack initiation criterion of Dang Van. The constants implied by the Dang Van procedure may be formally connected to the fatigue limit and mean stress dependence given by the Goodman rule, under conditions of uniaxial loading. The biaxial fatigue criterion of Sines is also compared with the Dang Van procedure. The similarity in the approaches may be further extended to permit finite initiation times to be estimated by the Dang Van criterion when the fatigue limit is exceeded.